72.6k views
5 votes
Calculus Questions using implicit differentiation to find the equation of the tangent line that is given curve at the 2, -1

Calculus Questions using implicit differentiation to find the equation of the tangent-example-1
User Ivan X
by
5.1k points

1 Answer

1 vote

The tangent line to the curve has slope equal to
(\mathrm dy)/(\mathrm dx) at the point (2, -1). We have, by implicit differentiation,


3y^2-6xy=2x+11\implies6y(\mathrm dy)/(\mathrm dx)-6y-6x(\mathrm dy)/(\mathrm dx)=2


\implies(\mathrm dy)/(\mathrm dx)=(2+6y)/(6y-6x)=(1+3y)/(3y-3x)

At the point (2, -1), the slope is then 2/9, so the tangent line has equation


y-(-1)=\frac29(x-2)\implies y=\frac29x-\frac{13}9

User Hilmi
by
4.7k points